2020
DOI: 10.1007/s13187-020-01861-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Peer Support for Cancer Prevention and Care: A Practice Review

Abstract: Research across the cancer care continuum indicates peer support can improve patient outcomes, yet little is known about how cancer peer support programs are implemented in practice. This study aimed to describe cancer peer support programs in "real world" (i.e., non-research) settings. A web search identified 100 programs in a wide variety of settings and locations; 48 published contact information on their website and were invited to participate in semi-structured interviews. Twenty-nine program leaders part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
(30 reference statements)
0
19
0
1
Order By: Relevance
“…Like many studies on peer support interventions for cancer, 9,10,18–21 our study shows that the primary activity of APs is to listen to patients and validate their emotions to facilitate their acceptance process of the disease and increase their ability to fight cancer in a positive way. This is done by sharing their own lived experiential knowledge and tips they acquired throughout their own journey with illness.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Like many studies on peer support interventions for cancer, 9,10,18–21 our study shows that the primary activity of APs is to listen to patients and validate their emotions to facilitate their acceptance process of the disease and increase their ability to fight cancer in a positive way. This is done by sharing their own lived experiential knowledge and tips they acquired throughout their own journey with illness.…”
Section: Discussionmentioning
confidence: 68%
“…For APs themselves, Brodar et al 19 mentioned that peer supporters could become emotionally charged following their encounters with patients as they can be reminded of their own experience with cancer. It was therefore suggested that there should be more support from clinical staff as well as from other peer supporters to create a sense of community which could comfort APs during difficult times and help them give meaning to their own experiences.…”
Section: Discussionmentioning
confidence: 99%
“… 36 This situation reflected the fact that support from peers rather than relatives was more acceptable to patients. 37 , 38 Peer support seems to work more easily for patients who do not interact directly with their healthcare providers, as they lack confidence in understanding the instructions of their healthcare providers. Therefore, it seems possible to set patients as the primary recipients of peer support in our previous preliminary SE programme.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a WeChat group for total laryngectomy patients may be established to learn and help deal with problems encountered at home, creating a sense of belonging and reducing anxiety caused by the insufficient routine follow-up care offered by healthcare professionals. Peer support can also improve patient prognoses (27). Asking patients with the same surgical experiences to present themselves in the preoperative or early postoperative period allows patients to see themselves in the future and increase their confidence in overcoming the disease.…”
Section: Early Social Support Helps Patients Cope Positively With the Transitionmentioning
confidence: 99%